Function and solution structure of the Arabidopsis thaliana RALF8 peptide. (13th May 2019) - Frederick, Ronnie O.; Haruta, Miyoshi; Tonelli, Marco; Lee, Woonghee; Cornilescu, Gabriel; Cornilescu, Claudia C.; Sussman, Michael R.; Markley, John L.
Abstract: We report the recombinant preparation from Escherichia coli cells of samples of two closely related, small, secreted cysteine‐rich plant peptides: rapid alkalinization factor 1 (RALF1) and rapid alkalinization factor 8 (RALF8). Purified samples of the native sequence of RALF8 exhibited well‐resolved nuclear magnetic resonance (NMR) spectra and also biological activity through interaction with a plant receptor kinase, cytoplasmic calcium mobilization, and in vivo root growth suppression. By contrast, RALF1 could only be isolated from inclusion bodies as a construct containing an N‐terminal His‐tag; its poorly resolved NMR spectrum was indicative of aggregation. We prepared samples of the RALF8 peptide labeled with 15 N and 13 C for NMR analysis and obtained near complete 1 H, 13 C, and 15 N NMR assignments; determined the disulfide pairing of its four cysteine residues; and examined its solution structure. RALF8 is mostly disordered except for the two loops spanned by each of its two disulfide bridges. Abstract : PDB Code(s):6NU4 ;